State aid for biofuels in Poland - Bartosz Bartniczak (Economic and Environmental Studies (E&ES), 2014)
State aid is one of the instruments through which a state can interfere in the economy. Therefore, state aid is a particular instrument of implementing policy. One of the objectives of environmental policy of the European Union is to hold up a climate change. This can be achieved, among others, by an increase in the production of biofuels and an increase in their share in the use of fuel. Therefore, state aid to support the production of biofuels is an instrument through which has come to increase the production of this type of fuel. The aim of this article is to demonstrate the importance of state aid for an increase in the production and use of biofuels in Poland. Indicated the legal basis for granting state aid in the area of biofuels. After were analysed the aid programmes which were implemented in Poland. The article introduces what effect was achieved by the implementation of these programmes.
Keywords: 330; state aid; biofuels; sustainable development; renewable energy